1975
DOI: 10.1017/s0022112075001607
|View full text |Cite
|
Sign up to set email alerts
|

Numerical prediction of incompressible separation bubbles

Abstract: A method is presented for performing detailed computations of thin incompressible separation bubbles on smooth surfaces. The analysis consists of finite-difference solutions to the time-dependent boundary-layer or Navier-Stokes equations for the flow in the immediate vicinity of the bubble. The method employs the McDonald-Fish turbulence model, to predict the development of the time-mean flow field, as influenced by the free-stream turbulence level. It also employs a viscous-inviscid interaction model, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Sj-e (13) where '" * 6 8 : 8 -8 re f (14) and (15) With the source strength, d/d~ (u ~o*) assumed to vary linearly over each subinterval, Sj_l to Sj' Eq. (13) is analytically integrated to give (16) ImaX-1 ++l:…”
Section: Ci!(ue 68 )Dementioning
confidence: 99%
“…Sj-e (13) where '" * 6 8 : 8 -8 re f (14) and (15) With the source strength, d/d~ (u ~o*) assumed to vary linearly over each subinterval, Sj_l to Sj' Eq. (13) is analytically integrated to give (16) ImaX-1 ++l:…”
Section: Ci!(ue 68 )Dementioning
confidence: 99%
“…Gerhart and Chima [16] Nreported that an attempt to apply an integral boundary layer scheme in an interaction procedure for treating subsonic turbulent separation had, to date, been unsuccessful. Differential solutions to the boundary layer equations were used in the interaction schemes applied to subsonic 4turbulent flow by Briley and McDonald [17], Carter [18], and Kwon and…”
Section: Imentioning
confidence: 99%
“…The Briley and McDonald study utilized a time-dependent analysis, whereas both Carter and Kwon and Pletcher employed inverse 4 boundary layer procedures. Carter [18] computed the separated flow on an axisymmetric body-sting juncture, whereas the other two studies [17,19] treated transitional midchord separation bubbles. Only [17] and [19] included comparisons with experimental data.…”
Section: Imentioning
confidence: 99%
“…For larger Reynolds numbers the numerical methods often fail to converge or are otherwise unable to yield meaningful solutions. Attempts have been made to apply these methods for the calculation of transitional separation bubbles [9,10] using empirical transition models to switch the solution from laminar to turbulent flow. However, these calculations have shown that the numerical solution is strongly dependent on the transition criteria used.…”
Section: Introductionmentioning
confidence: 99%